I'm confused on the following equivalent way of rewriting a two-component mixture.

Consider the two-component conditional mixture $$ F(z|x)=\lambda F_1(z|x)+(1-\lambda)F_2(z|x) $$ where all the $F$'s are conditional CDFs and $\lambda\in (0,1)$.

A1: Assume that $F(z|x)=0$ $\forall z\leq 0$.

A2: Assume that $\int_{\mathbb{R}}zdF_j(z|x)$ exists $\forall j\in \{1,2\}$.

Consider a random variable $Z_j$ with CDF conditional on $x$ equal to $F_j(\cdot|x)$ $\forall j \in \{1,2\}$.

Define the random variable $$ \epsilon_j\equiv Z_j-\int_{\mathbb{R}}zdF_j(z|x) $$ $\forall j \in \{1,2\}$. Let $G_j(\cdot|x)$ denote the CDF of $\epsilon_j$ conditional on $x$ $\forall j \in \{1,2\}$. Then, $$ F_j(z|x)=G_j\Big(z-\int_{\mathbb{R}}zdF_j(z|x)\Big|x\Big) $$ $\forall j \in \{1,2\}$. Hence we can rewrite $$ (\star) \hspace{1cm} F(z|x)=\lambda\times G_1\Big(z-\int_{\mathbb{R}}zdF_1(z|x)\Big|x\Big)+(1-\lambda)\times G_2\Big(z-\int_{\mathbb{R}}zdF_2(z|x)\Big|x\Big) $$

Question 1: I believe that A1 implies that $F_j(z|x)=0$ $\forall z\leq 0$ and $\forall j\in \{1,2\}$. Is this correct? If this is true, then can we say that, for example, A1 implies that $F_1(\cdot|x)$ and $F_2(\cdot|x)$ cannot be normal CDF?

If I'm correct about Question 1:

Question 2: A1 remains valid also under the new representation of the mixture $(\star)$. However, I can't see how $G_1\Big(z-\int_{\mathbb{R}}zdF_1(z|x)\Big|x\Big)$ and $ G_2\Big(z-\int_{\mathbb{R}}zdF_2(z|x)\Big|x\Big)$ can be zero for negative values of their arguments, given that the definition of $\epsilon_1,\epsilon_2$ does not prevent these two random variables from having negative realisations.


1 Answer 1


You are correct about Question 1. Since both $\lambda$ and $1-\lambda$ are positive, while $F_j(z\mid x)\ge0$, the only way for $\lambda F_1(z\mid x)+(1-\lambda)F_2(z\mid x)$ to be zero is if both $F_1(z\mid x)$ and $F_2(z\mid x)$ are zero. So it follows that $F_1(\cdot\mid x)$ and $F_2(\cdot\mid x)$ can never be the cdf of a Normal distribution.

For question 2, you are misreading the conclusion. The same argument as above shows that $G_j(z-\int zdF_j(z\mid x)\mid x)$ equals zero for all $z\le 0$. However, this does not imply that $G_j(t\mid x)$ equals zero for all $t\le0$, which seems to be your conclusion.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.